Narrativas femininas da vida em fuga : o discurso neo-orientalista em autobiografias e biografia de refugiadas sírias - Souza, Daniele dos Santos de (2023)
In recent years, there has been a significant increase in the publication of fictional, autobiographical, and journalistic literary works that address the flight of Syrian refugees from the Middle East to the West. This work aims to investigate the neo-orientalist discourse in the autobiographies Nujeen (2017), by Nujeen Mustafa and Christina Lamb (2017), Butterfly: from refugee to olympian, by Yusra Mardini (2022), and the biography A hope more powerful than the sea, by Melissa Fleming (2017). The starting point is the hypothesis that there is a trajectory in these stories that constructs Syrian refuge as the forced migration from the infernal East to the paradisiacal West. The research seeks to understand how the neoorientalist discourse manifests itself in those books and what its effects of meaning are on the female narrative of refuge. The main corpus of the research consists of excerpts and figures extracted from the analyzed books. The research understands these narratives as a privileged object of qualitative approach (DENZIN; LINCOLN, 2006). The Foucauldian conceptions of discursive formation, utterance, power relations, truth, and power (FOUCAULT, 2008; 2012) support the interpretation of the selected excerpts. This research is understood as transdisciplinary and inserted in the field of Applied Linguistics (MOITA LOPES, 2006). The theoretical framework conceptualizes structures such as Orientalism and Post/NeoOrientalism in order to demonstrate how such structures relate to the corpus. The results indicate that the stories contribute to the neo-orientalist discursive formation, which portrays the East as a place of barbarism, while the West is seen as a place of freedom and peace. This discursive construction confirms the initial hypothesis, however, the effects of meaning of these narratives are varied, since they can both marginalize other ways of life and also stimulate voluntary solidarity regarding the issue of refuge.